Remote Criminal Trial Procedures in Jordanian Law and Comparative Legislation - Faisal Abdullah Al-Muhareb Shdefat, Lect.Dr.Rafat; Jabbar Saleh, Dr.Ali (Basra studies journal, 2022)
This study summarized the problem of the physical presence of persons required to attend trials, prosecutions and investigations, and this comes through the electronic presence remotely, and after research, investigation and investigation we found that the Jordanian legislator took this modern system in trials and investigations and attended hearings, in an independent system in which he specified mechanisms, methods, conditions and powers of remote communication in the criminal case and this came in the system of using modern techniques in criminal procedures No. 96 of 2018 published on page 5606 of The issue of the Official Gazette No. 5529 of 2018/9/2 issued under article 158, paragraph 2 of the Code of Criminal Procedure assets and its amendments No. 9 of 1961, and this system included twelve articles, all of which revolve around remote communication and where to use the system, When applied by parties or not to the parties to the criminal proceedings, as well as the mechanisms for resorting to this system and the extent to which it can be resorted to by the court on its own or at the request of the parties to the case, and the Jordanian legislator as well as some legislation observes fair trial guarantees and provisions of confidentiality and publicity, as well as the results and effects of remote communication in national legislation, international conventions and treaties, and the opinion of the jurists touched on this study and showed the opinions in favor and opposition to remote communication, as well as the results and effects of remote communication, between Loss or maintenance of rights such as the right of defense, the right to plead and other rights, as well as the manifestation of effects that would be in the interest of remote communication.